ijee 2022
DOI: 10.48165/ijee.2022.58115
|View full text |Cite
|
Sign up to set email alerts
|

Investment and Resource Use Pattern followed by Dairy Farmers in Haryana

Abstract: Dairy sector plays a critical role in growth of rural India by providing livelihoodopportunities to millions of people. The present study was conducted in Zone-I and ZoneII of the Haryana state. District Kaithal and Karnal were selected from Zone I whereasSirsa and Hisar districts represented Zone II to study the investment and resource usepattern followed by the dairy farmers. To achieve the objective the primary data from the200 sampled dairy farms (divided into three categories i.e. small, medium and large … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 2 publications
0
3
0
Order By: Relevance
“…The The results are in accordance with the results of Sinha and Prasad (1966), Williams [1], Kaur [2], Gupta [3], Bembridge [4], Ambastha [5], Bhangoo and Kawer [6], Meena [7], Sharma [8] Singh and Singh [9], Dass, Sharma [10], Jha and Chauhan [11], Kadian and Kumar [12]. Kavaskar and Govind [13], Singh, Singh and Lakhera [14], JK Arneja CS and Singh DP.…”
Section: Communication Behaviour Of Wheat Growers (A) Wheat Productio...supporting
confidence: 90%
“…The The results are in accordance with the results of Sinha and Prasad (1966), Williams [1], Kaur [2], Gupta [3], Bembridge [4], Ambastha [5], Bhangoo and Kawer [6], Meena [7], Sharma [8] Singh and Singh [9], Dass, Sharma [10], Jha and Chauhan [11], Kadian and Kumar [12]. Kavaskar and Govind [13], Singh, Singh and Lakhera [14], JK Arneja CS and Singh DP.…”
Section: Communication Behaviour Of Wheat Growers (A) Wheat Productio...supporting
confidence: 90%
“…The reduction in milk yield (68.67%) shares the maximum percentage of economic loss followed by replacement cost (25.38%) and then treatment cost (5.95%) as seen from Table 5. The study conducted in Haryana revealed that the total investment made on dairy animal, the major proportion was covered by investment on feed and fodder, followed by concentrates and labours (Ghalawat, 2022).…”
Section: Interpretation and Reporting The Resultsmentioning
confidence: 99%
“…They examined farm investment decisions within specific production systems (e.g., rice, pineapple, cassava, tea, arboriculture, coffee, and coconut). In these studies, the aim was to explore farm investment dynamics under conditions of constrained resources, and the primary focus was placed on water and soil conservation practices and irrigation systems [29,[61][62][63].…”
Section: Trends In Farm Investment Research In Relation To Time Count...mentioning
confidence: 99%